Non‐thermal processes in coronae and beyond. Issue 1 (6th February 2013) - Poppenhaeger, K.; Günther, H. M.; Beiersdorfer, P.; Brickhouse, N. S.; Carter, J. A.; Hudson, H. S.; Kowalski, A.; Lalitha, S.; Miceli, M.; Wolk, S. J.
Abstract This contribution summarizes the splinter session "Non‐thermal processes in coronae and beyond" held at the Cool Stars 17 workshop in Barcelona in 2012. It covers new developments in high energy non‐thermal effects in the Earth's exosphere, solar and stellar flares, the diffuse emission in star forming regions and reviews the state and the challenges of the underlying atomic databases. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)